Star Trek VI : The Undiscovered Country - Nicholas Meyer; Takei, George, 1937-; Shatner, William; Nimoy, Leonard; Kelley, DeForest, 1920-1999.; Doohan, James, 1920-2005.; Koenig, Walter, 1936-; Nichols, Nichelle (USA Paramount Pictures, 1991)
After an explosion on their moon, the Klingons have an estimated 50 years before their ozone layer is completely depleted, and they all die. They have only 1 choice - to join the Federation, which will mean an end to 70 years of wars. Admiral James T. Kirk and crew are called upon to help in the negotiations because of their ""experience"" of the Klingon race. Peace talks don't quite go to plan, and eventually Kirk and McCoy are tried and convicted of assassination, and sent to Rura Penthe, a snowy hard-labour prison camp. Will they manage to escape ? And will there ever be peace with the Klingons ?
The crews of the Enterprise and the Excelsior must stop a plot to prevent a peace treaty between the Klingon Empire and the Federation.
Gene Roddenberry
Languages : English, German, Czech
Subtitles : English, Turkish, Arabic
Keywords: Mystery; SciFi; Action -- Tv Series